Wideband printed slot antenna with compact feeding network - Ng, Boon Chay. (2009)
The wideband slot antenna is a very interesting subject of study with many research and examples in recent years. A slot antenna is able to achieve a very large bandwidth on a relatively small and thin substrate. Because of its advantages, it has also been widely used in commercial applications such as satellite ground stations and beacons. A microstrip wideband slot antenna with compact feeding network is proposed here.